Relationship Between Social Support and Subjective Well-Being in Older Adults - Majid Goudarz; Mahshid Foroughan; Asghar Makarem; Vahid Rashedi (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: The main aim of this study was to investigate the relationship between social support and subjective well-being in the elderly referring to rehabilitation day centers in Tehran Province. Methods & Materials: This is a cross-sectional and correlational study. The study population was all the elderly referring to the rehabilitation day centers in Tehran Province. The sample size was 147 people, which were selected by random cluster sampling. To gather the data, Norbeck social support questionnaire, Philadelphia morale scale and a socio-demographic questionnaire were use. The Pearson and Spearman correlation coefficients, Chi-square, Independent t-test, Kruskal-Wallis, and ANOVA used for data analysis. Results: A total of 80 (54.4%) of sample were male. The mean (SD) age of older adults was 71.9(5.09) years and mean of subjective wellbeing was 8.65(2.28). The relationship between social support and subjective wellbeing was statistically significant (P=0.002, r=0.273). Conclusion: The findings showed significant relationship between social support and subjective well-being. It seems that having high social support will lead to better subjective well-being.